2009
DOI: 10.3748/wjg.15.5218
|View full text |Cite
|
Sign up to set email alerts
|

Biloma: An unusual complication in a patient withpancreatic cancer

Abstract: The term biloma describes an encapsulated collection of bile within the abdomen, usually secondary to bile duct disruption. The commonest causes reported in the literature are iatrogenic (secondary to hepatobiliary surgery), trauma or complications due to choledocholithiasis. A few cases have been reported as complications of cholangiocarcinoma or acute cholecystitis. We report the case of a 64-year-old man initially diagnosed with a non-obstructive malignancy of the pancreas, who developed a spontaneous intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 6 publications
0
32
0
3
Order By: Relevance
“…The biloma was identified on computed tomography and subsequently drained under ultrasound guidance. Forty-eight hours later, a stent was inserted endoscopically into his common bile duct and he made an uneventful in-hospital recovery without operation [10].…”
Section: Discussionmentioning
confidence: 99%
“…The biloma was identified on computed tomography and subsequently drained under ultrasound guidance. Forty-eight hours later, a stent was inserted endoscopically into his common bile duct and he made an uneventful in-hospital recovery without operation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous biloma is extremely rare, and choledocholithiasis and cholangiocarcinoma are reported as etiologic factors in most of these cases [3]. Rare causes have been reported, such as primary pancreatic malignancy [1], sickle cell disease [7,8] and gallbladder tuberculosis [9]. We emphasized that the spontaneous biloma was related with sclerosing cholangitis because there was no risk factor for developing a biloma in this case, including trauma, gallstone, abdominal intervention from biopsy or surgery, or malignancy in the CBD and/or periampullary region.…”
Section: Discussionmentioning
confidence: 99%
“…One currently suggested pathogenic mechanism is increased intraductal pressure due to obstructive lesions or infarctions of the bile ducts. Trivedi et al reported the first patient with spontaneous biloma, which occurred secondary to pancreatic malignancy, in 2009 [1]. They commented that an acute elevation in biliary pressure is unusual because of the relatively slow onset of ductal obstruction that occurs with pancreatic neoplasms [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations